- #1

- 14

- 0

If f(x) = 3x + 1

and g(x) = (x^2 + 5x)^-1/2

find g(f(x))

and g(x) = (x^2 + 5x)^-1/2

find g(f(x))

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter Aprilshowers
- Start date

- #1

- 14

- 0

If f(x) = 3x + 1

and g(x) = (x^2 + 5x)^-1/2

find g(f(x))

and g(x) = (x^2 + 5x)^-1/2

find g(f(x))

- #2

- 14

- 0

f(x) = 3x + 1

g(b) = (b^2 + 5b)^-1/2

Let b=f(x)=3x+1

Substitute 3x + 1 in for b:

g(b)=((3x+1)^2+5* (3x+1))^-.5

=(9x^2+6x+1+15x+5)^-.5

=(9x^2+21x+6)^-.5

g(f(x))= (9x^2+21x+6)^-.5

Please advise

- #3

HallsofIvy

Science Advisor

Homework Helper

- 41,847

- 966

Share: